Straw and Nominee Corporations in Real Estate Tax Shelter Transactions - Steven J. Stogel; David L. Jones (Washington University Law Quarterly, 1976)
During 1976, Congress placed some severe restrictions on tax shelter investments. In addition, even before Congress acted, the Internal Revenue Service (IRS) initiated its own attack on tax shelters. One IRS tactic to frustrate the objectives of tax shelter investments is to shift the incidence of taxation from one entity to another. This Article focuses primarily on one phase of the IRS attacks on real estate tax shelters. We will explore the history and legal foundation of the IRS’s present position, outline alternative arguments that can be raised by a real taxpayer involved in an IRS audit, and suggest possible tax planning considerations.
Keywords: Corporate taxes; Urban transportation – Federal aid; Agency; Corporations; Real property